2009
DOI: 10.1111/j.1530-0277.2009.01021.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Corpus Callosum Anomalies in Children With Prenatal Alcohol Exposure: An Extension of Previous Diffusion Tensor Imaging Findings

Abstract: Background-Several studies have now shown corpus callosum abnormalities using diffusion tensor imaging (DTI) in children with fetal alcohol spectrum disorders (FASD) in comparison with nonexposed controls. The data suggest that posterior regions of the callosum may be disproportionately affected. The current study builds on previous efforts, including our own work, and moves beyond midline corpus callosum to probe major inter-hemispheric white matter pathways with an improved DTI tractographic method. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
117
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(136 citation statements)
references
References 89 publications
(118 reference statements)
19
117
0
Order By: Relevance
“…Consistent with sMRI-revealed abnormal midline structures, a number of DTI studies have reported decreased FA in the corpus callosum of children and young adults with FASD, both as a whole structure [70] and in different subregions including the splenium, posterior mid-body and isthmus [71][72][73][74]. Children and young adults with FASD also exhibited lower FA in the right cingulum, bilateral inferior and superior longitudinal fasciculi (ILF and SLF respectively) and left thalamus [74][75][76]; the frontal, parietal and occipital lobes [73;77]; the medial prefrontal cortex and posterior cingulate cortex [78];…”
mentioning
confidence: 80%
“…Consistent with sMRI-revealed abnormal midline structures, a number of DTI studies have reported decreased FA in the corpus callosum of children and young adults with FASD, both as a whole structure [70] and in different subregions including the splenium, posterior mid-body and isthmus [71][72][73][74]. Children and young adults with FASD also exhibited lower FA in the right cingulum, bilateral inferior and superior longitudinal fasciculi (ILF and SLF respectively) and left thalamus [74][75][76]; the frontal, parietal and occipital lobes [73;77]; the medial prefrontal cortex and posterior cingulate cortex [78];…”
mentioning
confidence: 80%
“…Effects of prenatal alcohol exposure are linked to reduced white matter structural integrity in the cerebellum [83] and abnormalities in axial diffusivity [84] as early as infancy. In addition, subtle changes in FA have been associated with deficits in cognitive function including processing speed, math ability, executive function, and eye-blink conditioning [50,81,[85][86][87][88][89][90][91][92] A recent study was also able to demonstrate that structural white matter changes are linked to disturbances in functional connectivity while at rest [83].…”
Section: Integrity Of White Matter Tractsmentioning
confidence: 90%
“…The impact of prenatal alcohol exposure on measures of white matter microstructure shows that effects can be detected at multiple stages of development, are associated with behavior, and fall on a continuum ranging from mild to severe Abnormalities in the corpus callosum are frequently reported, but also in anterior-posterior fiber bundles, corticospinal tracts, and the cerebellum [79][80][81][82]. Effects of prenatal alcohol exposure are linked to reduced white matter structural integrity in the cerebellum [83] and abnormalities in axial diffusivity [84] as early as infancy.…”
Section: Integrity Of White Matter Tractsmentioning
confidence: 99%
“…Analyzing the samples addressed in these studies, it was clear that mostly they consisted of milder forms of FASD or of individuals who had been exposed to alcohol, but without a diagnosis, as stated in several studies. 13,14,17,20,31,34,35,46,47 The fact that the samples presented predominantly milder forms of FASD resulted in higher scores. This explains why some studies state that most individuals who were prenatally exposed to alcohol are not intellectually impaired.…”
Section: General Intelligencementioning
confidence: 99%